Impact of social media on mainstream journalism in Ghana - Acheampong, Richmond (Journal of Language, Literature, Social and Cultural Studies, 2024)
The study looked at how social media impact mainstream journalism in Ghana. It also determined the benefits and drawbacks of social media for mainstream journalism. 200 journalists were chosen at random from the Sunyani Municipality in the Bono region of Ghana using a purposive sampling technique for a phone and in-person interview to gather data. It was discovered, among other things, that all the respondents (i.e., 100%) believed that social media have positive impact on mainstream journalism, while most of the respondents (i.e., 80%) believed that social media have negative impact on mainstream journalism. As a result, it was suggested, among other things, that journalists use social media carefully to preserve the public’s trust in the media.